SARCOIDOSIS IN CHILDREN: MODERN VIEWS ON THE MECHANISM OF THE DEVELOPMENT, CLINIC, DIAGNOSTICS, TACTICS OF TREATMENT - Цимбаліста, О. Л. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
Sarcoidosis is met in children of all age groups. It belongs to the rares intersticial diseases of the lungs without pathognomic symptoms. There exists a hypothesis about genetic tendency to the development of sarcoidosis. Sarcoidosis develops as a result of disturbances in the immune system with the following development of systemic granulomatous reaction. In childen before 10 years of age sarcoidosis is manifested by extrathorathic signs, with generalized forms of large clinical polymorphism. In pre- and pubertal age sarcoidosis is manifested by intrathorathic forms with nondisparity of feebly marked clinical symptoms and considerable roentgenological changes in the lungs and lymph nodes of the mediastinum.